How To Build Relationships in the Music Industry: A Guide for Musicians - Hovinga, Arlette (Rowman & Littlefield Publishers, 2023)
Musicians: are you frustrated with promoters and other industry people leaving your emails unanswered? Do you wish to promote your projects but don’t know how to approach the right people? Promoters are often overwhelmed by hundreds of emails a day so getting that first moment of contact just right can be daunting. Emails are sometimes drafted poorly; social media presence is either lacking or spammy; and there is no real aim other than pushing for immediate results—except that isn’t how the industry works: We are not in the sales business. We are in the people business. That is the mantra of this book. Featuring interviews with dozens of industry professionals—many with diverse backgrounds and from across the globe— How to Build Relationships in the Music Industry presents valuable insights, do’s, don’ts, tips, and anecdotes that will help any musician present their next project in a way that works in the long term. Arlette Hovinga helps all musicians understand key characteristics of effective, professional communication in the music business which will ultimately lead to better relationships, more bookings, and a stronger following.